INVASIVE PLANTS IN THE FLORA OF MUREŞ COUNTY - SĂMĂRGHIŢAN MIHAELA; OROIAN SILVIA (Journal of Plant Development, 2012)
Invasive plants are those species that are capable of rapidly spreading at great distances from parent plants. Because of them, agriculture pays a huge annual tribute. These invasive plants might shortly become the most widely spread and destructive, as they seem to take best advantage from climate changes. They have a high phytocoenological competition capacity and rapidly adapt to new life conditions to the detriment of native plants. This paper aims to inform of the phenomenon of invasion of these alien plants, of their distribution and abundance in certain areas in Mureş County. If the monitoring of invasive plants receives particular international attention, in the Mureş County there is no concern for monitoring their invasion, for limiting their negative effects on the environment and human economy.The most rapacious and common invasive plants in the studied territory are presented in the paper.Because these species already occupy extremely large surfaces, the measures for fighting them are difficult and costly, and long-term measures for their control and elimination are required.